If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 + -1x = 3x + -5 Reorder the terms: 11 + -1x = -5 + 3x Solving 11 + -1x = -5 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 11 + -1x + -3x = -5 + 3x + -3x Combine like terms: -1x + -3x = -4x 11 + -4x = -5 + 3x + -3x Combine like terms: 3x + -3x = 0 11 + -4x = -5 + 0 11 + -4x = -5 Add '-11' to each side of the equation. 11 + -11 + -4x = -5 + -11 Combine like terms: 11 + -11 = 0 0 + -4x = -5 + -11 -4x = -5 + -11 Combine like terms: -5 + -11 = -16 -4x = -16 Divide each side by '-4'. x = 4 Simplifying x = 4
| 8-10x=78-38x | | 2x-3=x-2x-8 | | -7-5x=-7-7x | | 2+10x=110x+x | | 6x+7=91+6x | | 5x+21=7x+4 | | -15x+5y+30=0 | | 3x-3=-3+7x | | 3x^3-3000=0 | | x^2-3n-92=0 | | 3x^3=3000 | | x^2-3n-4=88 | | 2x^3-19x=0 | | 15x^2+16x+12=0 | | 4x-2=14x-23 | | 4x+40=11x+3 | | 9(2d+7)= | | 7x-6x+3=3 | | 1+9*4(30/2)= | | 4x^2-25x-36=0 | | 14x+1=29x+44 | | (2x+1)(x+4)=2(1-x)(5-x) | | 16e+6=8e-12 | | 4e+8=2e-15 | | (3x-8)(4x+9)= | | -6+4(11-5m)= | | 7p-1=5p+11 | | 3y-y-8y= | | 3x-7=7-4x | | 3x+4x+5x-2x=4x+5x+20 | | 9x-7=8x-1 | | 2x^3+9x^2+4x+6=0 |